The experiences of German social workers working with refugees. (January 2021) - Hagues, Rachel J; Cecil, David; Stoltzfus, Ken
Summary: This study examines the experiences of German social workers who provided services to refugees during the refugee crisis of 2014–2016. Interviews were conducted in 2016 in two regions of Germany, Berlin/Brandenburg ( n  = 18) and Würzburg (Bavaria; n  = 16). Researchers used a semi-structured interview guide complemented by a five-item Likert-type instrument. Questions explored Social Service Provider's Background and Training, Refugees' Needs, Role of Faith in Coping, and Recommendations for Universities and Churches and measure Effectiveness of Services, Adequacy of Resources, Benefits to Refugees, and Extent of Work-Related Stress . Findings: A thematic analysis indicates social workers feel Germany has effectively responded to paramount refugee needs. Social workers emphasize the importance of learning to see people "eye-to-eye, " cultivating empathy, cross-cultural competence, overcoming personal biases, and self-reflection. Applications: Findings suggest social workers who practice with refugees should devote attention to the development of personal attributes to facilitate effective service delivery (e.g. learning to respond empathetically, practicing self-reflection, and treating refugees as equals) and refining practical skills (e.g. study of refugee and immigration law nationally and internationally and development of cross-cultural knowledge and understanding). Suggestions include learning a greeting in another language or understanding gender roles in different cultures. The usefulness of cultural immersion gained by spending time abroad was highlighted; such experiences allow one to cultivate the ability to be open-minded, encourage the development of a capacity to empathize with members of under-represented groups, and prevent the tendency of seeing refugees or migrants as "the Other" (Said, 1978 ).